Between nationalism and transnationalism: entanglements of history, individual narrative, and memory in diaspora spaces in selected transnational fiction - Bosman, Sean James (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2020)
This thesis offers close readings and a comparative analysis of selected works by Abdulrazak Gurnah, Viet Thanh Nguyen, and Luis Alberto Urrea. The selected primary texts used are Gurnah's By the Sea (2000) and Gravel Heart (2017), Nguyen's The Sympathizer (2015) and The Refugees (2017), and Urrea's The Water Museum (2015) and The House of Broken Angels (2018). Analyses are informed by a conceptual framework that draws on critical works by Avtar Brah, J. U. Jacobs, Sarah Nuttall, Homi K. Bhabha, Judith Butler, Stuart Hall, Paul Ricoeur, Viet Thanh Nguyen, and Christopher B. Patterson. These theories are deployed to analyse how the selected works engage with the entanglements of history, individual narratives, and memory in the diaspora spaces they articulate. The thesis argues that the selected works indicate an emerging subgenre within the broader category of transnational literature. This subgenre rejects disempowering interpolations of transnational identities. Instead, it prioritises ethical forms of memory. These acknowledge that transnational subjects share at least partial accountability for the precarity they experience in diaspora spaces. The selected literature limns how this may be accomplished by rejecting the label of victim. In so doing, the selected literature also suggests that the elevation of transnationals to full ethical agency would enable them to exercise power in their diaspora spaces. All three authorial projects studied here also give rise to uncomfortable juxtapositions that suggest a mounting fear that, as nationalisms become more pronounced in the UK and the USA, transnationals may have to re-experience conditions from which they have already fled. The thesis concludes by identifying four additional areas of confluence amongst the selected literature worthy of future study.
Keywords: Literature and transnationalism; Gurnah, Abdulrazak, 1948-; Gurnah, Abdulrazak, 1948- -- By the sea; Gurnah, Abdulrazak, 1948- -- Gravel heart; Nguyen, Viet Thanh, 1971-; Nguyen, Viet Thanh, 1971- -- The sympathizer; Nguyen, Viet Thanh, 1971- -- The refugees; Urrea, Luis Alberto; Urrea, Luis Alberto -- The house of broken angels; Urrea, Luis Alberto -- The water museum